Determining the crystal-field ground state in rare earth heavy fermion materials using soft-x-ray absorption spectroscopy - Hansmann, Philipp; Haverkort, Maurits W. (Arxiv, 2007)
We infer that soft-x-ray absorption spectroscopy is a versatile method for the determination of the crystal-field ground state symmetry of rare earth Heavy Fermion systems, complementing neutron scattering. Using realistic and universal parameters, we provide a theoretical mapping between the polarization dependence of Ce $M_{4,5}$ spectra and the charge distribution of the Ce $4f$ states. The experimental resolution can be orders of magnitude larger than the $4f$ crystal field splitting itself. To demonstrate the experimental feasibility of the method, we investigated CePd$_2$Si$_2$, thereby settling an existing disagreement about its crystal-field ground state.